Zirconia changes after grinding and regeneration firing - Hatanaka, Gabriel R. [UNESP]; Polli, Gabriela S. [UNESP]; Fais, Laiza M. G. [UNESP]; Reis, Jose Mauricio dos S. N. [UNESP]; Pinelli, Ligia A. P. [UNESP] (Elsevier B.V., 2017)
Statement of problem. Despite improvements in computer-aided design and computer-aided manufacturing (CAD-CAM) systems, grinding during either laboratory procedures or clinical adjustments is often needed to modify the shape of 3 mol(%) yttria-tetragonal zirconia polycrystal (3Y-TZP) restorations. However, the best way to achieve adjustment is unclear. Purpose. The purpose of this in vitro study was to evaluate the microstructural and crystallographic phase changes, flexural strength, and Weibull modulus of a 3Y-TZP zirconia after grinding with or without water cooling and regeneration firing. Material and methods. Ninety-six bar-shaped specimens were obtained and divided as follows: as-sintered, control; as-sintered with regeneration firing; grinding without water cooling; grinding and regeneration firing with water cooling; and grinding and regeneration firing. Grinding (0.3 mm) was performed with a 150-m diamond rotary instrument in a high-speed handpiece. For regeneration firing, the specimens were annealed at 1000 degrees C for 30 minutes. The crystalline phases were evaluated by using x-ray powder diffraction. A 4-point bending test was conducted (10 kN; 0.5 mm/min). The Weibull modulus was used to analyze strength reliability. The microstructure was analyzed by scanning electron microscopy. Data from the flexural strength test were evaluated using the Kruskal-Wallis and Dunn tests (alpha=.05). Results. Tetragonal-to-monoclinic phase transformation was identified in the ground specimens; R regeneration firing groups showed only the tetragonal phase. The median flexural strength of as-sintered specimens was 642.0; 699.3 MPa for as-sintered specimens with regeneration firing; 770.1 MPa for grinding and water-cooled specimens; 727.3 MPa for specimens produced using water-cooled grinding and regeneration firing; 859.9 MPa for those produced by grinding; and 764.6 for those produced by grinding and regeneration firing; with statistically higher values for the ground groups. The regenerative firing did not affect the flexural strength. Weibull modulus values ranged from 5.3 to 12.4. The SEM images showed semicircular cracks after grinding. Conclusions. Adjustments by grinding in 3Y-TZP frameworks should be performed with water cooling, and regeneration firing should be undertaken to obtain a more reliable material.